Regional differences in baseline disease activity and remission rates following golimumab treatment for RA: results from the GO-MORE trial - Durez, Patrick; Pavelka, Karel; Lazaro, Maria Alicia; Garcia-Kutzbach, Abraham; Moots, Robert J; Amital, Howard; Govoni, Marinella; Vastesaeger, Nathan (Clinical rheumatology, 2018)
GO-MORE (NCT00975130) was a large open-label, multinational, multicenter, prospective phase 3 trial evaluating add-on therapy with golimumab in biologic-naïve patients with active rheumatoid arthritis (RA). The objective of this post hoc analysis was to examine regional differences in baseline disease activity and remission rates following golimumab treatment for RA. This was a planned, descriptive post hoc analysis of data from the GO-MORE trial. Baseline disease activity and remission were defined as moderate or severe based on EULAR criteria. This analysis included 3280 participants from the GO-MORE trial. All participants included in this analysis had high or moderate disease activity at baseline. At baseline, high disease activity was least common in Europe (71.0%), Canada (77.0%), and the Middle East (78.2%) and most common in Latin America (90.7%), South Africa (91.5%), and Asia (92.5%). Month 6 remission rates were highest in South Africa (29.1%), Europe (27.9%), and the Middle East (27.3%) and lowest in Canada (19.7%), Latin America (17.2%), and Asia (15.0%). Higher rates of remission in each geographical region generally corresponded with lower baseline disease activity. We suspect that access to care and implementation of the treat-to-target strategy were the most important determinants, but this apparent relationship needs to be confirmed in further studies that include a statistical analysis of prognostic indicators.
Keywords: dospělí; Geographic locations; Arthritis, Rheumatoid; Female; Rheumatoid arthritis; revmatoidní artritida; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; Antibodies, Monoclonal; lidé; Antirheumatic agents; Treatment Outcome; Aged, 80 and over; stupeň závažnosti nemoci; Methotrexate; prospektivní studie; Remission Induction; Male; Aged; methotrexát; Prospective Studies; indukce remise; Antirheumatic Agents; Young Adult; kombinovaná farmakoterapie; monoklonální protilátky; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Severity of Illness Index; Golimumab; antirevmatika; Clinical trial; Middle Aged; mladiství; Drug Therapy, Combination; Humans